(untitled) (Archaeologia Adriatica, 2022)
Only three Roman mirrors, that is their parts as none of them is complete, were found in the long-term excavations of the necropolis and settlement at the archaeological site of Velika Mrdakovica. We may say that two examples belong to common and popular forms (groups A and K in G. Lloyd Morgan’s typology), while one is atypical, exhibiting more luxurious craftsmanship, with closest analogy in the area of Germanic barbaricum - in the Hildesheim hoard. All mirrors from Mrdakovica belong to the period of the 1st and 2nd centuries AD and in addition to other finds, they stand as witnesses to lively trade exchange of the population of Velika Mrdakovica primarily with northern Italic production centers, but also with other parts of the Empire.